The relationship between sequential organ failure assessment (SOFA) score and mortality in covid-19 patients with ARDS - Setiyawan Setiyawan; Gleryn Viona Octaverlita; Dewi Suryandari (Jurnal Keperawatan Padjadjaran, 2023)
Background: The WHO declared a COVID-19 pandemic on January 30, 2020. Five percent of all patients with coronavirus disease-19 symptoms are emergency and critical cases of ARDS by 49% mortality. The SOFA score is an assessment in intensive care unit patients to determine the level of organ failure.Purpose:The research aimed to determine the relationship between SOFA scores and mortality in coronavirus disease-19 patients with ARDS.Methods: This type of research was quantitative with a retrospective cohort design. The population was coronavirus disease-19 patients with ARDS in the intensive care unit room at RSUD dr. Moewardi in January-September 2021 with 485 people. Eighty-three (83) respondents were selected through the purposive sampling technique. The research instrument used the SOFA scoring sheet. Results: The study on the characteristics of respondents revealed that 57.8% were male, the average age of respondents was 57.31 years and 57.8% with comorbid diseases. The abnormal SOFA scores were 96.4%, 91.6% mortality. The Chi-Square test showed a p-value of 0.018.Conclusion: There is a relationship between SOFA scores and mortality in coronavirus disease-19 patients with ARDS. SOFA score could be used as a predictor of mortality in coronavirus disease-19 patients with ARDS. SOFA score scores can describe the patient’s prognosis, because SOFA scores have an assessment of all six organ functions such as respiration (PaO2 / FiO2), blood pressure, creatinine and diuresis, bilirubin, platelets, and GCS, so that it is effective in assessing organ failure.